2002
DOI: 10.1152/ajpheart.00680.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of homocysteine on intracellular nitric oxide and superoxide levels in the renal arterial endothelium

Abstract: The present study was designed to test the hypothesis that homocysteine (Hcys) reduces intracellular nitric oxide (NO) concentrations ([NO](i)) and stimulates superoxide (O.) production in the renal arterial endothelium, thereby resulting in endothelial dysfunction. With the use of fluorescence microscopic imaging analysis, a calcium ionophore, A-23187 (2 microM), and bradykinin (2 microM) were found to increase endothelial [NO](i) in freshly dissected lumen-opened small renal arteries loaded with 4,5-diaminof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Prior investigations have called attention to the quenching of DAF-2 nitrosation by naturally occurring reducing agents such as Asc and GSH [7,46,67]. Consistent with these findings, our …”
Section: Do Antioxidants Such As Gsh or Asc Affect Daf Imaging?supporting
confidence: 90%
See 1 more Smart Citation
“…Prior investigations have called attention to the quenching of DAF-2 nitrosation by naturally occurring reducing agents such as Asc and GSH [7,46,67]. Consistent with these findings, our …”
Section: Do Antioxidants Such As Gsh or Asc Affect Daf Imaging?supporting
confidence: 90%
“…As we struggled with this seemingly straight-forward proposition, it became apparent that, while the development of diamino fluorophores represent a great analytical advance in NO bioimaging, there are a number of unresolved questions regarding the performance of these probes in biological tissues that impact their utility for the localization of sources and targets of NO. One important issue is that their sensitivity may be significantly limited in biological milieus by reducing agents such as ascorbate (Asc) and reduced glutathione (GSH), since these are known to scavenge nitrosating products such as N 2 O 3 , or their precursor NO 2. Several studies [6,46,66] have demonstrated this effect in buffer solutions, in which substantial drops or even a total abolishment of formation of the fluorescent triazole form DAF-2 T were observed. Yet, only modest inhibition of DAF-2 activation is observed within cultured cells containing comparable levels of reducing agents [66], and all other cell-culture or tissue studies published to date document its successful activation.…”
mentioning
confidence: 95%
“…E: relative eNOS mRNA (means Ϯ SE) normalized to relative smooth muscle alpha actin mRNA (n ϭ 7 in each group). mechanism for endothelium dysfunction in HHcy (2,8,21,28). This study reveals decreased eNOS expression and decreased ability to phosphorylate eNOS at S1179 with HHcy.…”
Section: Discussionmentioning
confidence: 60%
“…While the mechanistic link between HHcy and vascular disease is not entirely understood, one consistent finding is that HHcy reduces endotheliumdependent vasodilation (13,19,20,29,31), which is likely to be an underlying mechanism for its contribution to the vascular disease process. Evidence indicates that HHcy increases superoxide levels, thereby reducing the bioavailability of nitric oxide and the ability of arteries to dilate (2,8,21,28). It is unknown, however, whether chronic HHcy decreases vascular expression and activation of endothelial nitric oxide synthase (eNOS), the enzyme that produces nitric oxide.…”
mentioning
confidence: 99%
“…Not only does Hcy itself have prooxidant properties, but also accumulating evidence from clinical and basic science studies indicate that the primary pathogenesis of diseases associated with HHcy is a concomitant generation of superoxide anion, which inactivates NO (7,27,28,51,56,58). To date, several studies have suggested the existence of an interaction between Hcy and angiotensin II (ANG II) signaling as a pathway that contributes significantly to the potential oxidative stress in the vasculature (2,31).…”
mentioning
confidence: 99%